Widespread Distribution of the Sycamore Seed Bug Belonochilus numenius (Hemiptera: Heteroptera: Lygaeidae) Throughout the Republic of North Macedonia - Katerina Srebrova; Sterja Nacheski; Kiril Sotirovski (South-East European Forestry, 2019)
Background and Purpose: The sycamore seed bug, Belonochilus numenius (Say, 1831), was recorded for the first time in Europe in 2008, with finds in that same year in two separate locations in Spain and two in France. Since then, it has been reported to be present in 17 European countries. Once it reached Europe, the fast spread and establishment of this species was facilitated both by the increased plant trade and the relative frequency of plane trees (Platanus x acerifolia, P. orientalis and P. occidentalis) planted on a wide scale across the continent due to their popularity as urban and peri-urban trees. Materials and Methods: In the summer of 2019 we inspected urban, peri-urban and natural populations and groups of plane trees throughout North Macedonia, on a total of 44 sites, looking for presence of nymphs and adults of this insect on seed balls. We collected specimens and related data and made identification based on specific external characteristics typical of B. numenius. Results: We report the first record of B. numenius in the Republic of North Macedonia from July 2019, from P. x acerifolia in Skopje. Furthermore, after inspecting plane trees throughout the country we report the presence of this insect in 29 cities and towns, 3 peri-urban and in 1 natural population of P. orientalis. Conclusions: From the widespread distribution of this insect species, we conclude that it has entered the territory of North Macedonia many years prior, very likely soon after first records in Serbia in 2011 and Bulgaria in 2012, but has since been overlooked.